fast track: The Influance of Predisposing, Enabling, and Reinforcing Factors on Patient Behaivor in The Care and Treatment Plan of Inpatients at Baiturrahim Jambi Hospital - Oktavia, Melani; Girsang, Ermi; Nasution, Ali Napiah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
One of the main problems in the management of inpatients is the low behavior and noncompliance of patients with the care and treatment plan that has been prepared by the medical team. This is thought to be influenced by predisposing, enabling, and reinforcing factors. This study aims to analyze the influence of Predisposing, Enabling, and Reinforcing factors on the behavior of inpatients in the care and treatment plan. This research is quantitative research with a cross sectional study approach. The research was conducted at Baiturrahim Jambi Hospital. The population of this study were all 380 inpatients, while the sample obtained was 258 people. Sample withdrawal by purposive sampling. Data were analyzed through the stages of univariate analysis, then bivariate analysis using the Chi-Square test, and multivariate analysis using multiple logistic regression tests. The results showed that the variables of knowledge, attitude, trust, access to health facilities, hospital facilities, health worker feedback, and previous experience had a significant effect on the behavior of inpatients at Baiturrahim Jambi Hospital, while the availability of information and family support had no significant effect. Of all the variables, knowledge had the greatest influence, where patients with good knowledge had a 21.7 times higher chance of behaving well in following the care and treatment plan.